Information Source and Content – Drivers for Consumers' Valuation of Fairly Traded Foods - Liza von Grafenstein; Sarah Iweala; Anette Ruml (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2022)
To learn about the role of information content and source as catalysts to increase consumers' valuation of fairly traded foods, we conducted an online survey with 2,500 consumers representative of the German population. Within the online survey, respondents were randomly assigned to one of five information treatments or the control group. We employ the contingent valuation approach to measure the willingness-to-pay (WTP) premium for chocolate with the Fairtrade label compared to similar conventional chocolate. To estimate WTP and the outcome which measures the participants' purchasing intentions, we use ordinary least squares and interval regressions. We find that German consumers are willing to pay a high price premium for a Fairtrade label despite limited knowledge about the certification. This WTP is relatively robust to additional supportive information provision irrespective of the information source. However, the broader measure of behavior, the purchasing intention, can rise due to information provided by a retailer or the government. While a supportive statement by a university does not seem to incentivize the valuation of Fairtrade certified chocolate, we find that an unsupportive (zero effect) statement of the same source can discourage the purchasing intention. Our findings imply that policymakers and scientists need to mind the risk of generalized science communication and create information campaigns to increase purchasing frequency.
Keywords: M3; Q0; 330; Labor standards; sustainable consumption; ethical label; consumer knowledge; WTP; information treatment